Running the family firm : how the monarchy manages its image and our money - Clancy, Laura (Manchester University Press, 2021)
The British royal family has experienced a resurgence in public interest at the same time as global inequalities have expanded between 'the elites' and 'the rest'. Yet, the monarchy is absent from conversations about inequality. This is the only book arguing that we cannot talk about inequalities in Britain today without talking about the monarchy.